Decreasing predation rates and shifting predator compositions along a land‐use gradient in Madagascar's vanilla landscapes. Issue 2 (20th October 2020) - Schwab, Dominik; Wurz, Annemarie; Grass, Ingo; Rakotomalala, Anjaharinony A. N. A.; Osen, Kristina; Soazafy, Marie Rolande; Martin, Dominic A.; Tscharntke, Teja
Abstract: Land‐use change is the main driver of deforestation and land degradation resulting in the loss of biodiversity and ecosystem functioning in north‐eastern Madagascar. Vanilla, the region's main cash crop, is grown in agroforestry systems and may provide an opportunity for the conservation of biodiversity and ecosystem functioning. We used dummy caterpillars to assess predation rates and predator communities along a land‐use gradient including unburned old‐growth and forest fragments, herbaceous and woody fallows after shifting cultivation with fire usage, as well as rice paddies. The studied vanilla agroforests were either forest‐derived or fallow‐derived. Besides land‐use type, we considered the effects of land‐use history (unburned/burned), plot‐level parameters and the landscape composition to conclude on management recommendations. Old‐growth forest and forest fragments exhibited highest predation rates, which decreased with land‐use intensity. Overall, predation was higher in unburned land‐use types than in more open, previously burned habitats and rice paddies. High stem and vegetation densities were positively related to predation rates, but decreased with land‐use intensity. High forest cover in the surrounding landscape led to higher predation rates, while local structural parameters remained more important. The predator community was arthropod‐dominated across all land‐use types with ants responsible for between 33% and 69% of all predation events. Overall predator composition in old‐growth and forest fragments differed from all other land‐use types. Predation by Gryllacrididae (Orthoptera) was lower in all land‐use types, including forest‐derived vanilla, than in old‐growth forest and forest fragments, where they were important contributors to total predation. Vertebrate predation was low throughout. Synthesis and applications . Forested habitats feature higher predation rates and different predator compositions than other land‐use systems. Maintaining or restoring tree‐ and understorey‐rich vanilla agroforestry represents a viable tool in landscape conservation programmes as it has the potential to contribute to the conservation of predation as an important ecosystem function in both forest‐ and fallow‐derived agroforests. However, vanilla agroforestry has limited value in conserving forest‐specialized predator communities. While the establishment of tree‐rich agroforests on former fallow land is favourable for conservation ecosystem functioning, further forest transformation should be avoided. Abstract : Forested habitats feature higher predation rates and different predator compositions than other land‐use systems. Maintaining or restoring tree‐ and understorey‐rich vanilla agroforestry represents a viable tool in landscape conservation programmes as it has the potential to contribute to the conservation of predation as an important ecosystem function in both forest‐ and fallow‐derived agroforests. However, vanilla agroforestry has limited value in conserving forest‐specialized predator communities. While the establishment of tree‐rich agroforests on former fallow land is favourable for conservation ecosystem functioning, further forest transformation should be avoided. Résumé: Le changement d'utilisation des terres est le principal facteur de déforestation et de dégradation des terres, qui entraîne une perte de biodiversité et de fonctionnement des écosystèmes dans le nord‐est de Madagascar. La vanille, principale culture de rente de la région, est cultivée dans des systèmes agroforestiers et peut fournir une opportunité pour la conservation de la biodiversité et le fonctionnement des écosystèmes. Nous avons utilisé des chenilles artificielles pour évaluer les taux de prédation et les communautés de prédateurs le long d'un gradient d'utilisation des terres comprenant des vieilles forêts et des fragments de forêt non brûlés, des jachères herbacées et ligneuses issues des cultures sur‐brûlis, ainsi que des rizières. Les systèmes agroforestiers de vanille étudiés étaient soit dérivés de la forêt, soit de la jachère. En plus du type d'utilisation des terres, nous avons pris en compte les effets de l'histoire de l'utilisation des terres (non brûlées/brûlées), les paramètres au niveau des sites d'études et la composition du paysage pour tirer des recommandations de gestion. Les vieilles forêts et les fragments de forêts ont présenté les taux de prédation les plus élevés, qui ont diminué avec l'intensité de l'utilisation des terres. Dans l'ensemble, la prédation a été plus élevée dans les types d'utilisation des terres non brûlées que dans les habitats plus ouverts, précédemment brûlés, et les rizières. Les densités élevées de tiges et de végétation ont été positivement liées aux taux de prédation, mais ont diminué avec l'intensité de l'utilisation des terres. Une couverture forestière élevée dans le paysage environnant a entraîné des taux de prédation plus élevés, alors que les paramètres structurels au niveau local ont été encore plus importants. La communauté de prédateurs a été dominée par les arthropodes dans toutes les types d'utilisation des terres avec les fourmis occupant de 33 à 69% de tous les événements de prédation. La composition totale des prédateurs dans les vieilles forêts et les fragments de forêts a été différente de celle des autres types d'utilisation des terres. La prédation par les Gryllacrididae (Orthoptera) a été plus faible dans tous les types d'utilisation des terres, y compris le système agroforestier de vanille d'origine forestière, que dans les vieilles forêts et les fragments de forêts, où ils ont contribué considérablement à la prédation totale. La prédation par les vertébrés était faible partout. Synthèse et applications . Les habitats forestiers présentent des taux de prédation plus élevés et des compositions de prédateurs différentes de celles des autres systèmes d'utilisation des terres. Le maintien ou la restauration d'une agroforesterie de vanille riche en arbres et en sous‐bois constitue un moyen durable dans les plans de conservation des paysages car cela apporte le potentiel de contribuer à la conservation de la prédation en tant que fonction importante de l'écosystème dans les systèmes agroforestiers dérivées des forêts et des jachères. Cependant, l'agroforesterie de la vanille a une valeur limitée pour la conservation des communautés des prédateurs spécialistes des forêts. Bien que l'établissement des systèmes agroforestiers riches en arbres dans les vieilles jachères soit favorable pour la conservation du fonctionnement des écosystèmes, la transformation ultérieure de forêt devrait être évitée.